STUDI KASUS PENENTUAN RENDEMEN TEBU DI PABRIK GULA BUMN - Lamhot P. Manalu Istiawati (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT Condition of national sugar industry are systematically decreasing. The area, production, and produvtivity of sugarcane have been decreasing within last eight years, while sugar import has been increasing fast. Apropriate strategic plans to improve the above condition are required. Determination of rendemen by sugar mill(PG) is often based on asumption and is not measured correctly and transparently, of witch it becomes a source of conflicts between farmer and PG. This matter decreases the trust of farmer to PG and consequently the farmer is reluctant to plant sugar cane for better production. To overcome comprehensively, this research analyzes mechanism and management of current determination of rendemen. This research analyzes mechanism and management of current determination of rendemen. This study proposes a mechanism to improve rendemen of sugar that might be accepted by all parties. Keyword: rendemen determination, sugar, cane, sugar mill.